INTEGRATION OF RELIGION AND SCIENCE: A REVIEW OF THE UNDERLYING PHILOSOPHICAL AND SOCIOLOGICAL FACTORS - Pujiati Pujiati; Eva Dewi (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2026)
This article examines the intersection between religion and science, a topic of great relevance to the advancement of knowledge and the complexities of modern social life. It employs the literature study method, a data collection technique that involves studying and analyzing information from various relevant literature sources. This article examines the philosophical and sociological factors that underpin the development of a harmonious relationship between the two domains. Philosophically, this integration is triggered by the need to understand reality comprehensively through a synthesis of empirical and transcendental dimensions. An epistemological paradigm that emphasizes the complementarity of scientific rationality and spiritual values also strengthens integration efforts. From a sociological perspective, modern society's demand for moral meaning, ethics, and balance in the face of technological advances encourages ongoing dialogue between religion and science. In addition, social change, pluralism of knowledge, and the role of educational and religious institutions also shape a collaborative space for both. This article concludes that the integration of religion and science is not only possible but also necessary in order to create a more holistic, ethical, and relevant understanding of contemporary issues. ABSTRAKArtikel ini membahas Integrasi antara agama dan sains yg sangat relevan dalam konteks perkembangan pengetahuan dan dinamika kehidupan sosial modern. Dengan menggunakan Metode Study Pustaka yaitu teknik pengumpulan data yang dilakukan dengan mempelajari dan menganalisis informasi dari berbagai literatur yang relevan dengan penelitian. Artikel ini mengkaji faktor-faktor filosofis dan sosiologis yang berperan sebagai dasar terbangunnya hubungan harmonis antara kedua domain tersebut. Secara filosofis, integrasi ini dipicu oleh kebutuhan untuk memahami realitas secara komprehensif melalui sintesis antara dimensi empiris dan transendental. Paradigma epistemologis yang menekankan kesalingmelengkapi antara rasionalitas ilmiah dan nilai-nilai spiritual turut memperkuat upaya integrasi. Dari perspektif sosiologis, tuntutan masyarakat modern terhadap pemaknaan moral, etika, dan keseimbangan dalam menghadapi kemajuan teknologi mendorong dialog berkelanjutan antara agama dan sains. Selain itu, perubahan sosial, pluralisme pengetahuan, serta peran institusi pendidikan dan keagamaan turut membentuk ruang kolaboratif bagi keduanya. Artikel ini menyimpulkan bahwa integrasi agama dan sains bukan hanya memungkinkan, tetapi juga diperlukan, guna menciptakan pemahaman yang lebih holistik, etis, dan relevan terhadap persoalan-persoalan kontemporer.